2003
DOI: 10.1021/bc020091k
|View full text |Cite
|
Sign up to set email alerts
|

PDEPT:  Polymer-Directed Enzyme Prodrug Therapy. 2. HPMA Copolymer-β-lactamase and HPMA Copolymer-C-Dox as a Model Combination

Abstract: Polymer-directed enzyme prodrug therapy (PDEPT) is a novel two-step antitumor approach that uses a combination of a polymeric prodrug and polymer-enzyme conjugate to generate a cytotoxic drug rapidly and selectively at the tumor site. Previously we have shown that N-(2-hydroxypropyl)methacrylamide (HPMA) copolymer-bound cathepsin B can release doxorubicin intratumorally from an HPMA copolymer conjugate PK1. Here we describe for the first time the synthesis and biological characterization of a PDEPT model combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 20 publications
0
57
0
2
Order By: Relevance
“…In this case, a polymer -enzyme conjugate is prepared (PEGylated enzymes are already in routine clinical use (Table 1)) that will hydrolyse selectively a polymer drug linker within the tumour interstitium. The concept of PDEPT was exemplified first by an HPMA copolymer cathepsin B-PK1 combination , and subsequently a non-mammalian enzyme linker combination HPMA copolymer-b-lactamase combined with HPMA-copolymer-glycine-glycine-cephalosporindoxorubicin (Satchi-Fainaro et al 2003). We have also shown that HPMA copolymer-bound phospholipases can also be used to modulate drug liberation from liposomes .…”
Section: Novel Polymeric Anticancer Agents and Polymer-drug Combinationsmentioning
confidence: 97%
“…In this case, a polymer -enzyme conjugate is prepared (PEGylated enzymes are already in routine clinical use (Table 1)) that will hydrolyse selectively a polymer drug linker within the tumour interstitium. The concept of PDEPT was exemplified first by an HPMA copolymer cathepsin B-PK1 combination , and subsequently a non-mammalian enzyme linker combination HPMA copolymer-b-lactamase combined with HPMA-copolymer-glycine-glycine-cephalosporindoxorubicin (Satchi-Fainaro et al 2003). We have also shown that HPMA copolymer-bound phospholipases can also be used to modulate drug liberation from liposomes .…”
Section: Novel Polymeric Anticancer Agents and Polymer-drug Combinationsmentioning
confidence: 97%
“…Doxorubicin, linked through various bonds to HPMA, including amide and hydrazone [Rihova et al, 2001] bonds, has been widely investigated. Additionally, linkers containing enzymecleavable peptides have been employed in a polymerdirected enzyme pro-drug therapy (PDEPT) using peptides cleavable by cathepsin B [Satchi et al, 2001] and lactamase [Satchi-Fainaro et al, 2003]. Targeting of HPMA structures has been attempted with doxorubicin-functionalized particles using saccharides that promote liver uptake [Seymour et al, 1991] and mAb fragments [Ulbrich et al, 2004;Kovar et al, 2003].…”
Section: Polymersmentioning
confidence: 99%
“…Further developments in this field include chemotherapy with two-step polymer-drug combinations (e.g. polymer-directed enzyme prodrug therapy (PDEPT) [16] ).…”
mentioning
confidence: 99%